Numerical analysis of the flexural response of RC Beams strengthened with NSM-CFRP = Numeryczna analiza zginania belek żelbetowych wzmocnionych kompozytami włóknistymi wklejanymi w otulinę betonową - Khene, Ahmed; Mesbah, Habib Abdelhak; Chikh, Nasr-Eddine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this study, we have chosen to use a new technique of reinforcement with composite materials, namely the near surface mounted technique (NSM). The NSM technique consists in inserting strips of carbon fiber reinforced polymer (CFRP) laminate into slits made beforehand at the level of the concrete coating of the elements to be reinforced.
Keywords: NSM; strengthening; CFRP; numerical analysis; RC beams; wzmocnienia; włókna węglowe; kompozyt; analiza numeryczna; belka żelbetowa